Texas Terror : The Slave Insurrection Panic of 1860 and the Secession of the Lower South - Reynolds, Donald E., 1931- (Book collections on Project MUSE., 2007)
On July 8, 1860, fire destroyed the entire business section of Dallas, Texas. At about the same time, two other fires damaged towns near Dallas. Early reports indicated that spontaneous combustion was the cause of the blazes, but four days later, Charles Pryor, editor of the Dallas Herald, wrote letters to editors of pro-Democratic newspapers, alleging that the fires were the result of a vast abolitionist conspiracy, the purpose of which was to devastate northern Texas and free the region's slaves.